KEPENTINGAN INDONESIA MELAKUKAN KERJA SAMA INDONESIA AUSTRALIA CONVERHENSIVI ECONOMIC PARTNERSHIP AGREEMENT (IA-CEPA) - Fajar Khoirurrizal Fahri; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia and Australia are two neighbouring countries, but the economic interaction between the two countries has been considered unfruitful because of the trade constraints such as, tariff, hazy rules and procedures, technical barriers of commerce, investment restrictions, strict visa requirement for Indonesia citizens and a difference in assessments for job competence. This study illustrate how both countries work together to reduce the barriers through a comprehensive bilateral cooperation known as Indonesia Australia Comprehensive Economic Partnership Agreement (IA-CEPA). This research uses qualitative research methods that is explanative and The data obtained from literatures such as book, articles from journals, media, and the internete. In analyzing this topic, the writer applies the prespective of liberalism and the theory of cooperation in the form of free trade are (FTA). This research shows that IA-CEPA has resulted eliminates trade barriers in the form of tariffs, technical barriers, limits on the amount of investment, simplifies administration, adds visas quota, and collaborates in the assessment of labor competencies, and others economics discussions so that it can be said to be comprehensive. Indonesia feels this cooperation is important as an effort to face economic globalization and can represent its national interests so that it is willing to agree. Key Words: Bilateral Cooperation, IA-CEPA, Indonesia, Australia, Economic Relations, Trade Barriers, Liberalism Interdependent, National interests.